If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -4) + 2x = 4x + -6 Reorder the terms: 4(-4 + x) + 2x = 4x + -6 (-4 * 4 + x * 4) + 2x = 4x + -6 (-16 + 4x) + 2x = 4x + -6 Combine like terms: 4x + 2x = 6x -16 + 6x = 4x + -6 Reorder the terms: -16 + 6x = -6 + 4x Solving -16 + 6x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -16 + 6x + -4x = -6 + 4x + -4x Combine like terms: 6x + -4x = 2x -16 + 2x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 -16 + 2x = -6 + 0 -16 + 2x = -6 Add '16' to each side of the equation. -16 + 16 + 2x = -6 + 16 Combine like terms: -16 + 16 = 0 0 + 2x = -6 + 16 2x = -6 + 16 Combine like terms: -6 + 16 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| (6y+5)(y-2)= | | 13x+7=6x+14 | | -3+7q=-7+9q | | -(1+6m)+6m=-11+3(r-7) | | Y=(5t^2)*(5t^3) | | -2(3)(-5)= | | 3(7-4x)=-39 | | 12=96 | | 3x+3+55=180 | | 4(5x-7)=52 | | 4x^3-34x^2+70x-25=0 | | -5s-9=-2s | | 2x^2-12x=32x-192 | | 3(-7+7x)=168 | | 5(8-8x^2)=8 | | 6y-28=4y-12 | | -7u=-8u+6 | | f(x)=ln(x+1) | | 12x+36=-3x-81 | | -6-5x=4x-51 | | -5+2x-8x+4x=40 | | 5x-(3x-(13-2x))=(6x-14)-189 | | 10+6x=15-7x | | -3-7v=-6v | | 2b+16=-6+4 | | 7x+9=5x+31 | | 2b-12=19b-15 | | 3-8x+3x+5=31 | | 8x+10=15-9 | | P^2=8p | | 3lnx-5lnx=3 | | 5+7x+3x=75 |